Region‐specific disturbed iron redistribution in Cushing's disease measured by magnetic resonance imaging‐based quantitative susceptibility mapping. (14th March 2022) - Jiang, Hong; Li, Zhenghao; Yang, Wenjie; Sun, Yuhao; Yan, Fuhua; Sun, Qingfang; Wei, Hongjiang; Bian, Liuguan
Abstract: Objectives: Cushing's disease (CD) is most common endogenous Cushing's syndrome. This study aimed to assess iron alternations in deep grey matter in CD. Design: A cross‐sectional study was performed. Patients: In this study, 48 active CD patients, 39 remitted CD patients and 52 healthy control (HC) subjects underwent magnetic resonance imaging. Measurements: Quantitative susceptibility mapping (QSM). Results: Decreased susceptibility values were found in the bilateral putamen, caudate, red nucleus, subthalamic nucleus and pulvinar nuclei of the thalamus (TL‐PLV) in active and remitted patients with CD compared with HCs. Interestingly, in remitted patients with CD, altered susceptibility values were significantly correlated with altered brain volumes in TL‐PLV, while TL‐PLV may play an essential role as a general regulatory hub for adaptive and flexible cognition. Conclusion: Chronic exposure to hypercortisolism may be related to iron distribution and significantly correlated with altered brain volumes and clinical features in patients with CD.